Microwave-Assisted Synthesis and Docking Studies of Triazole Derivatives: Evaluating Anticancer Properties - Madhuri Desai (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background Study: This study investigates the synthesis of triazole derivatives using microwave-assisted methods and evaluates their potential as anticancer agents through docking simulations. Microwave irradiation offers rapid and efficient synthesis of these derivatives, known for their pharmacological activities in cancer therapy. Docking studies predict their interactions with key biomolecular targets, providing insights into their therapeutic potential. Microwave-assisted synthesis has revolutionized organic chemistry by enhancing reaction rates and yields. Triazole derivatives are of particular interest due to their diverse pharmacological properties, including anticancer activities. Docking simulations complement experimental studies by predicting molecular interactions, guiding the design of more effective therapies. Methodology and Materials: Triazole derivatives were synthesized using microwave irradiation, employing various synthetic routes. Characterization involved spectroscopic techniques (NMR, IR, MS) to confirm chemical structures and assess purity. Docking simulations utilized computational tools to predict binding affinities and modes of interaction with cancer-related biomolecular targets. Results: Synthesized triazole derivatives exhibited promising yields and purity, confirmed by analytical methods. Docking studies identified several compounds with potential anticancer activity, showing favorable binding energies and interactions with target proteins implicated in cancer progression. Comparative analyses with standard drugs highlighted novel compounds worthy of further investigation.